The temperature dependent TCAD and SPICE modeling of AlGaN/GaN HEMTs - Yuan, Li (2013)
In this work, the temperature dependent TCAD and SPICE modeling platform of AlGaN/GaN HEMTs has been established by using Sentaurus TCAD and Silvaco UTMOST IV. Typically, the temperature co-efficient of series resistance, trans-conductance, sub-threshold swing and gate/buffer leakage has been extracted from the TCAD simulation. Based on that, the compact SPICE device model of HEMTs has been built up, which can be used for DC/transient SPICE simulation and power electronics circuit demonstration. The SPICE modeling results agree well with our TCAD simulation, indicating good revealing of the physical mechanisms of the AlGaN/GaN HEMTs' operation.